Eksplorasi Persepsi Guru Terhadap Modul Ajar Biologi Berbasis Inkuiri Di Sma Negeri 5 Pekanbaru - Ramadhani, Hafifa Nur; Mellisa; Hidayati, Nurkhairo (CV. SINAR HOWUHOWU, 2026)
Abstract Biology learning requires active student involvement in the concept discovery process, yet the availability of teaching materials facilitating such activities remains limited. This study aims to explore biology teachers' perceptions regarding the development of inquiry-based teaching modules at SMA Negeri 5 Pekanbaru. The approach used was mixed methods with a sequential explanatory design. The subjects consisted of three biology teachers selected using purposive sampling technique. Data collection was conducted through perception questionnaires and semi-structured interviews. Data analysis techniques employed descriptive statistics for quantitative data and thematic analysis for qualitative data. The results showed that teacher perception was classified as positive with an overall average percentage of 77.50%. The indicator of module needs and relevance obtained the highest score of 81.67%, indicating a high urgency for the availability of innovative teaching materials. Meanwhile, the support and barriers indicator obtained the lowest score of 73.33%. Qualitative analysis revealed that although teachers had a good conceptual understanding of inquiry, classroom implementation was constrained by time management and administrative burdens. There is a discrepancy between teachers' pedagogical competence in designing modules and the technical operational constraints in the field. This study concludes that teachers strongly require ready-to-use inquiry-based teaching modules and expect expert assistance in their development to enhance the quality of biology learning.